Allergic Comorbidities of Korean Patients with Atopic Dermatitis: A Nationwide Cross-Sectional Study - Lee, Yeon Seok; Lee, Yu Jin; Lee, June Hyunkyung; Choi, Jae Eun; Han, Tae Young (Annals of dermatology, 2023)
KCI Citation Count: 0